Komik Fotokopian Indonesia 1998 – 2001 - Imansyah Lubis (ITB Journal Publisher, LPPM ITB, 2009)
Comics have become an integrated part in Indonesian history. It also has a good prospect to continuously growing in modern media. As one of the medium of free expression, Indonesian comics has been experiencing its ups and downs over several decades. The growth of photocopied comics in Indonesia in year 1990s has become one of the important phases of a whole Indonesian comics development and movement. As a milestone, it is interesting to know further about the contexts of these photocopied comics. The main sources for this research are the photocopied comics collected by writer himself, and thereby this research only focused at a specific period of time between the years 1998 to 2001. Data being analyzed includes the internal contexts of comic, consisted of its 'soul' (theme, story, casting, and story background), and its 'body' (illustration), and the external contexts (illustrators, production - distribution, and readers). One of the challenges in doing this research is that not all of the photocopied comics mentioned what year it is being published. However, those comics are still analyzed considering they are in the same timeline with the rest. Writer is also perforced to exclude some comics, because they were not photocopied, but printed. This research tries to keep its focus to internal and external contexts of these photocopied comics, with sociological and anthropological approach.As a general conclusion, it can be said that social mind theme and theme from photocopied comics are complementary one another. Humor comic type and men gender comic figure from middle-weight predominates, so do with urban setting. The influence of manga visual style can be easily found, and most of comics’ creators are men who lived in Jakarta.By the end of this article, the author projects Indonesian comics prospect - not only its photocopied ones - in the future.